1981
DOI: 10.1139/g81-025
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Meiosis in Hybrids. Ii. Triploid Hybrids

Abstract: Methods are developed that allow a quantitative determination of relative affinity in triploid hybrids. This results in new insights into the analysis of meiosis in hybrids, genomic relationships and the assignment of genome symbols. The separate recording of open and closed chromosome figures in meiotic analyses is shown to be essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 4 publications
3
82
0
Order By: Relevance
“…Alonso & Kimber (1981) observed that curves showing the relationship of x to the number of ring bivalents and x to the number of trivalents always intersect at an x-value of 0.8. Thus, if the number of trivalents is greater than the number of ring bivalents (x is less than 0.8), then the hybrid can be considered to be a 3:0 type.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Alonso & Kimber (1981) observed that curves showing the relationship of x to the number of ring bivalents and x to the number of trivalents always intersect at an x-value of 0.8. Thus, if the number of trivalents is greater than the number of ring bivalents (x is less than 0.8), then the hybrid can be considered to be a 3:0 type.…”
Section: Resultsmentioning
confidence: 99%
“…In other hybrids, in which it has not previously been possible to identify the chromosomes from different genomes, the extent to which homoeologous and homologous pairing occurs has been estimated using mathematical models. One such model (Alonso & Kimber, 1981;Chapman & Kimber, 1992) was applied to the present data in order to determine the accuracy of its predictions. This model was chosen as it has been found to show results similar to other mathematical models.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The necessary conditions for its application are that the hybrid to be investigated is polyploid to allow the opportunity for preferential pairing, that the cross can be made and the plants brought to flowering, and that the chromosome figures formed at metaphase I of meiosis can be identified. In this series of papers the models for meiotic analysis developed by Alonso & Kimber (1981), Kimber & Alonso (1981) and Espinasse & Kimber (1981) for triploid, tetraploid and pentaploid hybrids, respectively, are being re-examined and extended. Chapman & Kimber (1992a) demonstrated an advantage in weighting meiotic figure frequencies by the number of chromosomes each contains when calculating the merit function to be minimized during optimization.…”
Section: Introductionmentioning
confidence: 99%